2012
DOI: 10.1242/jcs.104497
|View full text |Cite
|
Sign up to set email alerts
|

CDK Regulates Septin organization through Cell-cycle-dependent Phosphorylation of the Nim1-related Kinase Gin4

Abstract: SummaryCyclin-dependent kinases (CDKs) regulate septin organization in a cell-cycle-dependent manner in yeast. However, the mechanism remains unclear. Here, we show that the Candida albicans CDK Cdc28 phosphorylates the Nim1-related kinase Gin4, a known septin regulator, activating its kinase activity, which in turn phosphorylates the Sep7 septin. Gin4 contains a cluster of CDK phosphorylation sites near the kinase domain. Replacing serine/threonine with alanine in these sites prevents Gin4 activation, weakens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(69 citation statements)
references
References 63 publications
(116 reference statements)
4
56
0
9
Order By: Relevance
“…In several systems, phosphorylation of septins has been shown to modulate septin dynamics (24,25,41,42). Shs1p is by far the most heavily phosphorylated septin in S. cerevisiae and A. gossypii (22,25); thus, we have focused extensive effort on analysis of the regions containing and residing near the Shs1p phosphorylation sites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In several systems, phosphorylation of septins has been shown to modulate septin dynamics (24,25,41,42). Shs1p is by far the most heavily phosphorylated septin in S. cerevisiae and A. gossypii (22,25); thus, we have focused extensive effort on analysis of the regions containing and residing near the Shs1p phosphorylation sites.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated in many systems, from yeast to mammals, that septins are posttranslationally modified, and these modifications function in septin organization and activity (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Phosphorylation is by far the most common modification found on septins, and septins rely upon kinases to achieve normal structure and function (19,22,24,25,27,28,31,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, a series of studies have shown that CDKs control C. albicans hyphal growth by phosphorylating components in key cellular machines that execute polarized growth (23), including the Cdc42 GTPase module (24), actomyosin ring components (59), septins (28,60), endocytic machinery (29), and the Cbk1/ Mob2 complex in the regulation of Ace2 and morphogenesis network (61). Recently, Sudbery and his colleagues have reported that the hypha-specific Hgc-Cdc28 phosphorylates and regulates Sec2 and Exo84, two downstream components of the vesicular transport pathway during C. albicans hyphal growth (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about how septins are regulated or what signals may lie downstream of septins in C. albicans. The cyclindependent kinase Cdc28 and the Nim1 kinase Gin4 have demonstrated roles in regulating the septin ring during yeast-like and hyphal growth (11,12), but it is quite likely that further elements act upstream of septins to regulate their localization and stability. No pathways working downstream of septins have yet been identified in C. albicans, although the Hsl1 and Swe1 protein kinases, which coordinate responses to septins in S. cerevisiae, are present in C. albicans.…”
mentioning
confidence: 99%